2022
DOI: 10.1111/pai.13819
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood allergy linked with development of attention deficit hyperactivity disorder and autism spectrum disorder

Abstract: Allergic disorders including allergic dermatological diseases especially atopic dermatitis (AD), rhino-conjunctivitis, asthma, food, and drug allergies are common chronic morbidities in pediatric patients.The prevalence of allergic diseases is constantly increasing in the last decades, especially in high developed countries. 1 Though the exact pathogenesis of allergic disorders is not yet defined, it appears that genetic and environmental factors play a role in their development. 2 In addition to physical disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Three articles were excluded because of data duplication and small sample sizes. Ultimately, 12 articles satis ed the criteria for inclusion in the systematic review and meta-analysis [14][15][16][17][18][19][20][21][22][23][24][25] . These eligible studies comprised 5 case-control studies, 4 cross-sectional studies, and 3 cohort studies.…”
Section: Inclusion Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles were excluded because of data duplication and small sample sizes. Ultimately, 12 articles satis ed the criteria for inclusion in the systematic review and meta-analysis [14][15][16][17][18][19][20][21][22][23][24][25] . These eligible studies comprised 5 case-control studies, 4 cross-sectional studies, and 3 cohort studies.…”
Section: Inclusion Of Studiesmentioning
confidence: 99%
“…Two studies [20][21] described the prevalence of ADHD in patients with AR and non-AR patients, with a combined sample size of n = 132,561. The meta-analysis results indicated that the likelihood of developing ADHD in the AR group was 3.96 times greater than that in the control group (OR: 3.96, 95% CI: 3.80-4.12) (Fig.…”
Section: Relationship Between Ar/non-ar Patients and Adhdmentioning
confidence: 99%
“…Recently, the increasing prevalence of early childhood allergic diseases has coincided with an increase in childhood-onset NDDs 8 , 9 . Consequently, numerous studies have focused on exploring the connection between the immune and nervous systems, particularly during early infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Eczema is an inflammatory cutaneous condition with a 20% lifetime prevalence, whereby 80% of affected individuals develop it before age 6 (Nemet et al, 2022; Weidinger et al, 2018). Concerning ADHD, a study using population-based surveys of 354,416 children in the United States found that eczema was associated with an approximately 50% increased risk of later acquiring ADHD compared to those without eczema (Strom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the first to examine the association between ASD, ADHD, and two of the most common skin disorders. As the prevalence of those with either ADHD or ASD has increased, so too have many cutaneous disorders, with several studies finding significant associations between allergic disorders (“asthma, rhinitis, conjunctivitis, skin, food, or drug allergy”) and ADHD or ASD (Nemet et al, 2022). Awareness of the symptoms that characterize ADHD and ASD can grant insight into how patients with these neurodevelopmental disorders interface with the healthcare system and adhere to recommended treatments.…”
Section: Introductionmentioning
confidence: 99%